The use of Sumudu transform for solving certain nonlinear fractional heat-like equations - Atangana, Abdon; Kilicman, Adem (Hindawi Publishing Corporation, 2013)
We make use of the properties of the Sumudu transform to solve nonlinear fractional partial differential equations describing heat-like equation with variable coefficients. The method, namely, homotopy perturbation Sumudu transform method, is the combination of the Sumudu transform and the HPM using He’s polynomials. This method is very powerful, and professional techniques for solving different kinds of linear and nonlinear fractional differential equations arising in different fields of science and engineering.